Pelatihan Japanese Language Proficiency Test (JLPT) N4 dan Pengenalan Budaya Kerja bagi Siswa LPK Harapan Putra Bandung Indonesia Malang - cahyono, agus; Efrizal (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
Japanese language learners at vocational training institutions, particularly those in Malang, require training to prepare for the Japanese Language Proficiency Test (JLPT) N4, which will be held in December 2023. This training aims to prepare LPK students to understand the exam system and practice questions. Additionally, the community service team introduces Japanese work norms and ethics. The community service team conducts training and seminars for prospective migrant workers, held over 10 sessions in the ITSK RS dr. Soepraoen Malang classroom. From the JLPT simulation results, only 46.6 percent passed the simulation, so in the next batch, there needs to be an increase in Japanese language learning, both in terms of quantity and quality, with a focus on JLPT questions. Keywords: Japanese language; JLPT; training; LPK; Malang